Failed States and Ungoverned Spaces. Issue 1 (November 2016) - Lynch, Marc
State failure and proxy war have consumed key Arab states such as Iraq, Libya, Syria, and Yemen, with massive humanitarian consequences. Local power struggles have been exacerbated by regional and international interventions. The next American administration must act to resolve these wars and assist the reconstruction of shattered states. Rather than new military interventions, the United States should focus on the international enforcement of military de-escalation to accomplish these goals. This article explores the distinctive challenges for U.S. policy in each of these conflicts.